INFLUENCE OF DIMENSIONLESS WELLBORE RADIUS ON DIMENSIONLESS PRESSURE AND PRESSURE DERIVATIVES - Patrick Ebelechukwu Akuagwu; Wilfred Chinedu Okologume (Romanian Journal of Petroleum & Gas Technology, 2023)
Effects of wellbore radius on pressure derivatives of a vertical oil well is a major concern to oil and gas industry operators who intend to execute fluid production from a vertical oil well. Reservoir deliverability depends on several factors: the dimensionless wellbore radius. This study examines the influence of the dimensionless wellbore radius on the pressure and pressure derivative. A set of polynomials was implemented to calculate the dimensionless pressure variable and the pressure derivative. The polynomials were put into a computer program developed in the study to create a fast means through which the effect of wellbore radii can be studied easily. However, when several dimensionless radii were used as input parameters for the developed computer program, it was observed that the lower the dimensionless wellbore pressure, the higher the pressure derivative and vice versa. Also, lower dimensionless time yielded higher values of the dimensionless pressure variable. Results from the developed computer model were validated by comparing results from the model to those obtained from a published article while using the same input parameters (tD and rWD). Moreover, the percentage error was estimated to be less than 0.02%.